Multi-Criteria Experimental Comparison of Batteries Circuital Models for Automotive Applications - Nobile, Giovanni; Cacciato, Mario; Scarcella, Giuseppe; Scelba, Giacomo (Communications - Scientific letters of the University of Zilina, 2018)
Electrochemical batteries used in energy storage systems provide a significant contribution to the development of smart grids and green transportation. In recent years, intensive research activities have been oriented to the optimal management of energy storage systems for power electronics applications in fast growing industrial sectors as EVs and HEVs. The accurate modeling of electrochemical batteries is fundamental in the design of control algorithms applied to energy storage systems. Focusing on automotive applications, in this paper a comprehensive analysis of ESS models based on equivalent electric circuits using a multi-criteria approach is presented. An extensive experimental validation has been carried out to evaluate the performance of battery models in automotive applications.